2008
DOI: 10.1175/2007jamc1599.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Indirect Soil Moisture Assimilation and Direct Surface Temperature and Humidity Assimilation on a Mesoscale Model Simulation of an Indian Monsoon Depression

Abstract: This study investigates the impact of the Flux-Adjusting Surface Data Assimilation System (FASDAS) and the four-dimensional data assimilation (FDDA) using analysis nudging on the simulation of a monsoon depression that formed over India during the 1999 Bay of Bengal Monsoon Experiment (BOBMEX) field campaign. FASDAS allows for the indirect assimilation/adjustment of soil moisture and soil temperature together with continuous direct surface data assimilation of surface temperature and surface humidity. Two addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…This rather complicated dynamical and hydrological processes of the MD www.intechopen.com provide some challenges to the regional and global climate models. For example, to properly simulate extreme rainfall under global warming, these need to be well simulated by regional or global climate models (e.g., Ratnan and Cox 2006, Vinodkumar et al 2008). …”
mentioning
confidence: 99%
“…This rather complicated dynamical and hydrological processes of the MD www.intechopen.com provide some challenges to the regional and global climate models. For example, to properly simulate extreme rainfall under global warming, these need to be well simulated by regional or global climate models (e.g., Ratnan and Cox 2006, Vinodkumar et al 2008). …”
mentioning
confidence: 99%
“…They found also that whenever there is a local forcing, the analysis-nudging alone, without the observation-nudging, may be harmful because it could limit the model's natural ability to produce finer-scale features. Something different has been found by Vinodkumar et al (2008) and Vinodkumar et al (2009) who studied the Indian monsoon region. They reported a general improvement of the meteorological parameters with surface and satellite data assimilation even in these strongly largescale-induced conditions.…”
mentioning
confidence: 62%
“…-as other authors have indicated (Vinodkumar et al, 2008 for example), it is probably worth trying the assimilation of surface variables together with vertical profiles of temperature and relative humidity, or maybe also using the latent heat nudging approach (see for instance the work of Leuenberger and Rossa, 2007) or assimilation of satellite data and fluxes or GPS data. Those modifications could be helpful to adjust the entire PBL in order to correct the precipitation field.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Ramamurthy and Carr 1987;Krishnamurti et al 1991), the impact of assimilating land-surface information is relatively poorly studied (e.g. Vinodkumar et al 2008).…”
Section: Introductionmentioning
confidence: 99%